A role for the claustrum in cognitive control. Issue 12 (December 2022) - Madden, Maxwell B.; Stewart, Brent W.; White, Michael G.; Krimmel, Samuel R.; Qadir, Houman; Barrett, Frederick S.; Seminowicz, David A.; Mathur, Brian N.
Abstract : Early hypotheses of claustrum function were fueled by neuroanatomical data and yielded suggestions that the claustrum is involved in processes ranging from salience detection to multisensory integration for perceptual binding. While these hypotheses spurred useful investigations, incompatibilities inherent in these views must be reconciled to further conceptualize claustrum function amid a wealth of new data. Here, we review the varied models of claustrum function and synthesize them with developments in the field to produce a novel functional model: network instantiation in cognitive control (NICC). This model proposes that frontal cortices direct the claustrum to flexibly instantiate cortical networks to subserve cognitive control. We present literature support for this model and provide testable predictions arising from this conceptual framework. Highlights: Modern neuroscience approaches have expanded investigation into the functional role of the claustrum, one of the most highly connected regions of the brain. Emerging data across rodent studies demonstrate that the claustrum is required for optimal cognitive performance and synchronizes distant cortical areas. Human whole-brain functional imaging data demonstrate the claustrum activates during difficult versions of a cognitive task and with the emergence of task-positive cortical networks. We propose a functional role for the claustrum in cortical network instantiation underlying cognitive control.